EFEKTIVITAS PROBLEM BASED LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH DAN SELF-EFFICACY: SYSTEMATIC LITERATURE REVIEW - Agustin, Nia; Novaliyosi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effectiveness of Problem Based Learning (PBL) on students’ mathematical problem-solving ability and self-efficacy through a Systematic Literature Review (SLR). The study followed the PRISMA guidelines and collected articles from Google Scholar, Portal Garuda, and DOAJ published between 2018 and 2026. A total of 11 primary studies that met the inclusion criteria were analyzed descriptively. The findings indicate that PBL consistently has a positive and significant effect on students’ mathematical problem-solving ability and improves students’ self-efficacy. In addition, both variables were found to be interrelated in supporting successful mathematics learning. These results suggest that PBL is effective in simultaneously developing students’ cognitive and affective aspects. However, this study is limited by the relatively small number of studies and the dominance of quantitative approaches.